ANOMALOUS WIDENING OF 5434.5 LINE IN SUNSPOTS: SUPER-STRONG MAGNETIC FIELDS? - Lozitsky, V. G.; Osipov, S. M.; Stodilka, M. I. (Одеські астрономічні публікації, 2020)
We present results of spectral observations of two sunspots in six metal lines near Fe I 5434.5 Å, which have effective Lande factors g eff from – 0.014 to 2.14. The observations were made on July 8 and August 25, 2015, with the ATsU-5 telescope of GAO NAS of Ukraine using a circular polarization analyzer and spectra registration with the SBIG ST-8300 CCD camera. The following line parameters are compared: observed splitting of I ± V profiles, the width and depth of the Stokes I profiles. Significant differences of the measured magnetic field strengths B eff were found in separate places of the spots and by lines with different g eff values. The Fe I 5434.5 Ǻ line (g eff = –0.014) shows measurable splitting in some locations of the sunspots, which corresponds to the magnetic field B obs ≈ 20 kG. Comparison of the widths and depths of the line profiles revealed several special places in the sunspots, where the Fe I 5434.5 Ǻ line was expanded additionally by ≈ 15–35%, whereas other lines with larger Lande factors did not have such a feature. One of the reasons for this expansion could be a sharp and local increase of turbulent velocities, but no active processes such as solar flares or significant Doppler flows were observed at these locations. A semi-empirical model constructed for the first sunspot by FeI 5434.5 line using inverse code with Tikhonov`s stabilizers shows an anomalous feature – the maximum of microturbulent velocities in the upper photosphere and the temperature minimum zone instead of the usual small increase of microturbulence at these heights. This may be the effect of very strong magnetic fields of mixed polarity or unresolved turbulent structures. As to first case, the estimated value of the magnetic field in such locations of sunspots is 10 5 G, which requires additional careful verification.